Genomic evidence for MHC disassortative mating in humans. Issue 1899 (20th March 2019) - Dandine-Roulland, Claire; Laurent, Romain; Dall'Ara, Irene; Toupance, Bruno; Chaix, Raphaëlle
Abstract : Although pervasive in many animal species, the evidence for major histocompatibility complex (MHC) disassortative mating in humans remains inconsistent across studies. Here, to revisit this issue, we analyse dense genotype data for 883 European and Middle Eastern couples. To distinguish MHC-specific effects from socio-cultural confounders, the pattern of relatedness between spouses in the MHC region is compared to the rest of the genome. Couples from Israel exhibit no significant pattern of relatedness across the MHC region, whereas across the genome, they are more similar than random pairs of individuals, which may reflect social homogamy and/or cousin marriages. On the other hand, couples from The Netherlands and more generally from Northern Europe are significantly more MHC-dissimilar than random pairs of individuals, and this pattern of dissimilarity is extreme when compared with the rest of the genome. Our findings support the hypothesis that the MHC influences mate choice in humans in a context-dependent way: MHC-driven preferences may exist in all populations but, in some populations, social constraints over mate choice may reduce the ability of individuals to rely on such biological cues when choosing their mates.